PROBLEMATIKA TAKLID DAN IJTIHAD MENURUT SYAIKH AL-BUTHI DAN NASHIRUDDIN AL-ALBANI - Farid Adnir (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
The purpose of this journal was made so that we can find out how the two central figures gave fatwas and their ways of thinking regarding taklid in various religious issues. textually, both in the Qur'an and As-Sunnah, various kinds of scholars define ijtihad, namely devoting all abilities in seeking zhanni syar'i laws, within the limit until he feels unable to exceed his efforts , then what is the view of Shaykh Said Ramadhan Al-Buthi in matters of ijtihad or taklid that every person when encountering a fiqhiyyah problem, has only two choices, namely between thinking and doing ijtihad on his own while continuing to look for arguments that can answer, or taqlid following the opinion of the previous mujtahid. Ijtihad cannot just read one or two books, and even without a teacher who has scientific knowledge. If that happens, then the religious law will be damaged, whereas according to Shaykh Albani's view it is very combating the method of taklid, taklid is accepting whatever someone says, usually a scholar or expert in knowledge without questioning the validity of the basis of the basis of the law. Perseverance in the science of hadith causes Sheikh al-Albani not to be bound with certain sects. In fact, in principle, Sheikh al-Albani is bound by 4 schools of thought at once.